2022
DOI: 10.15642/jiis.2022.16.2.455-479
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of Religious Moderation in Indonesian Higher Education Institutions

Abstract: Typologies of religious moderation implementation in several State Islamic Higher Education and Public Higher Education are an interesting subject to discuss. The typologies can demonstrate the road model of educational institutions in building nationality and diversity. This study aims to analyze the typologies of religious moderation practiced at PTKI and PTU with a focus on studies at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The challenge for Islamic Education Institutions in developing religious moderation lies in the commitment of schools and teachers currently (Aziz et al, 2021). Schools need to innovate and create an environment that enables students to understand and internalize the value of religious moderation (Burhanuddin & Ilmi, 2022;Solahudin et al, 2023). Referring to several studies on strengthening moderate attitudes in foreign countries, as described in the findings above, constructivist pedagogy can be an alternative approach to implementing religious moderation.…”
Section: The Potential Of Constructivist Pedagogical Approach In Stre...mentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge for Islamic Education Institutions in developing religious moderation lies in the commitment of schools and teachers currently (Aziz et al, 2021). Schools need to innovate and create an environment that enables students to understand and internalize the value of religious moderation (Burhanuddin & Ilmi, 2022;Solahudin et al, 2023). Referring to several studies on strengthening moderate attitudes in foreign countries, as described in the findings above, constructivist pedagogy can be an alternative approach to implementing religious moderation.…”
Section: The Potential Of Constructivist Pedagogical Approach In Stre...mentioning
confidence: 99%
“…This involves the formulation of an eclectic curriculum and religious activities and applying the pesantren model to maintain the value of Islamic moderation. Burhanuddin & Ilmi's (2022) research on the typology of implementation of religious moderation in higher education found several types of implementation, such as through student pesantren programs, the integration-interconnection paradigm of Islamisation of science, and the internalization of religious moderation values in Islamic Religious Education courses. Research by Imamah (2023) and Maya et al (2023) explains that religious moderation is implemented by inserting religious moderation values as a basis for teaching specific courses or subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Kegiatan mendidik bukan hanya peran dunia pendidikan saja tetapi pada setiap elemen masyarakat harus melakukan kegiatan pendidikan, karena mendidik merupakan tugas setiap manusia bukan hanya tugas pendidik saja. (Yunof Candra, 2019) Indonesia menempatkan pendidikan agama, khususnya pendidikan agama Islam, sebagai peran paling penting dalam memerangi krisis multidimensi bangsa, di mana Indonesia memiliki jumlah pemeluk Islam terbesar di dunia (Burhanuddin, 2022;Helmy, 2021;Lestari, 2019;Nasir, 2021). Pendidikan agama Islam diyakini dapat membangun karakter dan peradaban bangsa yang baik (Nuhayati, 2020).…”
Section: Pendahuluanunclassified